Alterations in the Retinal Vascular Network and Structure in MOG Antibody-Associated Disease: An Optical Coherence Tomography Angiography Study. Issue 4 (27th December 2021) - Yu, Jian; Huang, Yongheng; Quan, Chao; Zhou, Lei; ZhangBao, Jingzi; Wu, Kaicheng; Zong, Yuan; Zhou, Xujiao; Wang, Min
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: To determine retinal vessel density in patients with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Methods: Twenty-five patients with MOGAD and 20 healthy participants were enrolled. Patients with MOGAD were divided into myelin oligodendrocyte glycoprotein antibody (MOG-Ab)-positive eyes with a history of optic neuritis (ON; MOG-Ab-ON+ group) or without a history of ON (MOG-Ab-ON− group). Visual function, retinal vessel densities, and thickness were measured. Results: The retinal nerve fiber layer, parafoveal ganglion cell and inner plexiform layers, and vessel densities in the peripapillary and parafoveal areas were significantly decreased in the MOG-Ab-ON+ eyes compared with healthy eyes and MOG-Ab-ON− eyes (all P < 0.05). An increasing number of ON episodes was associated with greater decreases in these variables (all P < 0.05). Visual field mean deviation was not significantly decreased in patients with a history of 1 or 2 episodes of ON, although the relative decreases in retinal nerve fiber layer thickness, parafoveal ganglion cell and inner plexiform layer thickness, peripapillary vessel density, and parafoveal vessel density reached 33.1%, 23.2%, 17.0%, and 11.5% (all P < 0.05), respectively, in eyes with 2 episodes of ON. The mean deviation was significantly correlated with peripapillary vessel density ( P < 0.05) after adjustment for other variables. Best-corrected visual acuity was not significantly correlated with optical coherence tomography variables (all P > 0.05). Conclusions: MOG-Ab-associated ON was associated with significant decreases in retinal structure and vessel density, without significant deteriorations in visual function. The peripapillary vessel density might predict the visual outcomes in patients with MOG-Ab-associated ON.